Are Experts Right or are They Members of Expert Groups?. (2nd November 2018) - Collins, Harry
ABSTRACT: I describe an approach to the meaning of expertise that grows out of sociological approaches to the analysis of science such as 'sociology of scientific knowledge'. This approach was introduced to counter certain political interpretations of the movement associated with that new perspective. Here, 'Studies of Expertise and Experience' is described and contrasted with standard philosophical and psychological approaches to expertise. It is suggested that it leads in new and interesting directions and suffers from fewer conceptual problems than these standard approaches.